European trade with lower-income countries and the relative wages of the unskilled: an exploratory analysis for West Germany and the UK - Matthias Lücke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper develops a Heckscher-Ohlin-type framework in which relative factor prices are affected by output prices as well as by total factor productivity growth. The empirical analysis finds no evidence that the relative prices of unskilled-labour- intensive manufactures, adjusted for total factor productivity growth, declined after 1970 to depress the wages or employment opportunities (in the presence of an inflexible wage structure) of unskilled labour. Similarly, neither in West Germany nor in the UK did changes in the commodity composition of foreign trade reflect a sustained rise in the stock of unskilled labour in the rest of the world (which they should if labour markets were strongly affected by growing developing country exports).
Keywords: F14; J31; 330; Außenwirtschaft; Außenwirtschaftstheorie; Lohn; Ungelernte Arbeitskräfte; Faktorpreis; Deutschland; Großbritannien; Entwicklungsländer